Asymmetric information and imperfect competition in lending markets - Gregory S. Crawford; Nicola Pavanini; Fabiano Schivardi (University of Zurich, Department of Economics, 2015)
We measure the consequences of asymmetric information and imperfect competition in the Italian lending market. We show that banks' optimal price response to an increase in adverse selection varies with competition. Exploiting matched data on loans and defaults, we estimate models of demand for credit, loan use, pricing, and firm default. We find evidence of adverse selection and evaluate its importance. While indeed prices rise in competitive markets and decline in concentrated ones, the former effect dominates, suggesting that while market power can mitigate the adverse effects of asymmetric information, mainstream concerns about its effects survive with imperfect competition.
Keywords: 330